Potential of Cellulose-Based Superabsorbent Hydrogels as Water Reservoir in Agriculture - C. Demitri; F. Scalera; M. Madaghiele; A. Sannino; A. Maffezzoli (International Journal of Polymer Science)
The present work deals with the development of a biodegradable superabsorbent hydrogel, based on cellulose derivatives, for the optimization of water resources in agriculture, horticulture and, more in general, for instilling a wiser and savvier approach to water consumption. The sorption capability of the proposed hydrogel was firstly assessed, with specific regard to two variables that might play a key role in the soil environment, that is, ionic strength and pH. Moreover, a preliminary evaluation of the hydrogel potential as water reservoir in agriculture was performed by using the hydrogel in experimental greenhouses, for the cultivation of tomatoes. The soil-water retention curve, in the presence of different hydrogel amounts, was also analysed. The preliminary results showed that the material allowed an efficient storage and sustained release of water to the soil and the plant roots. Although further investigations should be performed to completely characterize the interaction between the hydrogel and the soil, such findings suggest that the envisaged use of the hydrogel on a large scale might have a revolutionary impact on the optimization of water resources management in agriculture.